“You must teach us about living!”: an exploration of the problem of ‘living’, in Holocaust education - Pattle, Annabel (2019)
Holocaust Education is an education of crisis. The Holocaust is unrepresentable and incomprehensible therefore to speak of a Holocaust ‘education’ is to speak within a paradox.